Where Culture Meets Technology: Developing a Digital Folklore E-Book for EFL Reading Comprehension - Alicia Ferani Solong; Sophia Binendyk; Hendrik J. Maruanaya (Eastasouth Institute, 2026)
Integrating culturally grounded narratives into EFL instructional materials plays a vital role in enhancing students’ reading comprehension and engagement. This study investigated the feasibility and instructional effectiveness of an Ambonese digital folklore e-book for junior high school students at SMP Negeri 13 Ambon. Using the 4D Research and Development model (define, design, develop, disseminate), 105 students participated in small- and large-scale trials, while three experts evaluated the e-book’s design validity using structured validation instruments. Data were collected through expert validation, pre- and post-tests, and student perception questionnaires. The expert evaluation indicated high feasibility, with a mean score of 3.39 (excellent), reflecting strong content organization, visual design, and reading activities. N-gain analysis showed consistent medium improvement, with values of 0.58 (small-scale) and 0.65 (large-scale), alongside an increase in mean scores from 52 to 83. Student responses were highly positive, with 65–85% indicating strong interest, usefulness, moral value, and motivation. These findings demonstrate that the digital folklore e-book is valid, effective in improving reading comprehension, and capable of fostering engaging learning experiences. Therefore, it is suitable as an instructional resource for junior high school students, supporting both cognitive development and cultural understanding.